2018
DOI: 10.3390/ijms19041168
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiologic Roles of Epstein–Barr Virus-Encoded MicroRNAs in Human Lymphomas

Abstract: Epstein–Barr virus (EBV) is a human γ-herpesvirus implicated in several human malignancies, including a wide range of lymphomas. Several molecules encoded by EBV in its latent state are believed to be related to EBV-induced lymphomagenesis, among which microRNAs—small RNAs with a posttranscriptional regulating role—are of great importance. The genome of EBV encodes 44 mature microRNAs belonging to two different classes, including BamHI-A rightward transcript (BART) and Bam HI fragment H rightward open reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 121 publications
0
27
1
Order By: Relevance
“…77 Some studies have focused on the role of EBVencoded miRNAs and NKTCL pathogenesis. 78,79 One of these studies showed that an EBVexpressed miRNA (i.e. BART9 miRNA) is overexpressed in two NKTCL cell lines, and it promotes cellular growth by upregulating LMP1, an oncogene encoded by EBV.…”
Section: Noncoding Rnas In Nktcl Pathogenesismentioning
confidence: 99%
“…77 Some studies have focused on the role of EBVencoded miRNAs and NKTCL pathogenesis. 78,79 One of these studies showed that an EBVexpressed miRNA (i.e. BART9 miRNA) is overexpressed in two NKTCL cell lines, and it promotes cellular growth by upregulating LMP1, an oncogene encoded by EBV.…”
Section: Noncoding Rnas In Nktcl Pathogenesismentioning
confidence: 99%
“…Their contributions to viral pathogenesis and oncogenesis have been shown in many EBV-associated lymphomas [3,4]. Diverse cellular pathways including p53, B-cell signaling, immune activation, cell proliferation, and apoptosis are now known to be regulated by EBV miRNAs in lymphomas [5].…”
Section: Introductionmentioning
confidence: 99%
“…The PI3K/Akt/mTor pathway plays an essential role in the oncogenic viral cycle, from entry to protein synthesis transcription, apoptosis inhibition and oncogenic transformation. Further recent studies of Epstein Barr virus [37] also suggest primary membrane-related mechanisms, but which remain to be explored.…”
Section: Resultsmentioning
confidence: 99%